Distributed Leadership and Empowerment Influence on Teachers Organizational Commitment. - Mohd Ali, Hairuddin; Yangaiya, Salisu Abba (2015)
The purpose of this study is to examine the influence of school distributed leadership (DL) on teachers’ organizational commitment (TC) and to investigate if teachers’ empowerment (TE) mediates the relationship between distributed leadership and teachers’ organizational commitment. The study distributed 750 questionnaires to the sampled respondents out of which 550 or 73% were returned. However, after excluding questionnaires with serious missing information 499 usable returned questionnaires were used for this study. The study used SPSS and AMOS (versions 16.0) to analyze the data collected. The findings indicate that school distributed leadership has considerable effect on teachers’ organizational commitment (standardized coefficient .39). The study also proved that teacher empowerment considerably mediates the relationship between distributed leadership and teachers’ commitment (standardized coefficient .26). As for the implications, the findings of this study bring to the fore the need for head teachers, zonal directors and other stakeholders to find more means of distributing leadership in secondary schools in order to enhance teachers’ commitment and empowerment. The study is one of the few studies conducted to investigate the influence and the relationship of distributed leadership on teachers’ organizational commitment and the mediating role of teachers’ empowerment on distributed leadership and teachers’ commitment, in Katsina state in particular and Nigeria in general.